Design and memory optimization of hybrid gate diffusion input numerical controlled oscillator - Reddy, Gujjula Ramana; Perumal, Chitra; Kodali, Prakash; Rajanna, Bodapati Venkata (Institute of Advanced Engineering and Science, 2023)
The numerically controlled oscillator (NCO) is one of the digital oscillator signal generators. It can generate the clocked, synchronous, discrete waveform, and generally sinusoidal. Often NCOs care utilized in the combinations of digital to analog converter (DAC) at the outputs for creating direct digital synthesizer (DDS). The network on chips (NOCs) are utilized in various communication systems that are fully digital or mixed signals such as synthesis of arbitrary wave, precise control for sonar systems or phased array radar, digital down/up converters, all the digital phase locked loops (PLLs) for cellular and personal communication system (PCS) base stations and drivers for acoustic or optical transmissions and multilevel phase shift keying/frequency shift keying (PSK/FSK) modulators or demodulators (modem). The basic architecture of NCO will be enhanced and improved with less hardware for facilitating complete system level support to various sorts of modulation with minimum FPGA resources. In this paper design and memory optimization of hybrid gate diffusion input (GDI) numerically controlled oscillator based on field programmable gate array (FPGA) is implemented. compared with NCO based 8-bit microchip, memory optimization of hybrid GDI numerically controlled oscillator based on FPGA gives effective outcome in terms of delay, metal-oxide-semiconductor field-effect transistors (MOSFET’s) and nodes.